Estudo da solidificação do aço rápido M2 em diferentes lingotes e seus efeitos na microestrutura e propriedades mecânicas finais - Delgado, Magno Pereira (Universidade Federal de São Carlos, 2011)
The high speed steels are mostly applied in cutting tools, like drills, cores and top milling cutter. Its microstructure is composed by martensite, with high hardness, strong tempering resistance and disperses carbides on its final work condition. The main alloys elements used in the M2 high speed steel are the Mo, W and V. It was studied 3 types of ingots: 150 Kg, 850 Kg and 1700Kg, all of them with a H/D relation (high/ transversal section) = 3. Also, its was studied two of the principal process parameters of the high speed steels, ingot sizes and hot deformation, analyzed by microstructure sizes and mechanical properties. It was analyzed the effects of the ingots sizes, cells sizes and cooling rates in the ingots microstructures and its effects in the microstructure and mechanical properties after the hot deformation by the forging process. The cooling rates, related to the ingot sizes, are variables that affect directly the size and carbides distribution after the forging process, and they will act directly in the final properties of these materials, especially in the wear resistance and toughness. The results show that, even the smaller ingots provide higher cooling rates; its dimensions are not big enough to provide a sufficient reduction area degree in the hot deformation, able to provide adequate mechanical properties. Also, too small ingots are not industrial productiveness. In the other hand, the big ingots, in spite of allow higher deformation rates, and provide more productivity; generate segregation that compromised the final toughness in the ingots. The commitment between the productiveness and the quality are essential and must be considered.
High speed steel M2 solidification study in diferent ingots and its effects in the microestructure and mechanical properties
Keywords: Aço; Microestrutura; Taxas de resfriamento; Propriedades mecânicas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA